Analysis of Employee's Awareness Level of Occupational Health and Safety at PT. Works of Fertilizer Land - Fajar, Afzalul; Yusnaidi (Cattleya Darmaya Fortuna, 2023)
The questionnaire was designed to collect data on understanding of safety procedures, use of personal protective equipment, participation in safety training, and other relevant aspects. The collected data were analyzed using descriptive statistical techniques to describe the profile of employee awareness of occupational health and safety. The results of this study are expected to provide a better understanding of employees' level of awareness towards occupational safety as well as areas where improvements or interventions may be needed to improve safety conditions in the workplace.The approach used is a descriptive approach method, namely by means of interviews, direct observation, and also a review of literature. This aims to determine the level of awareness of employees working at PT. KTS against K3 that will occur. The results of the analysis obtained, the authors state that the employees at PT. KTS is aware of occupational health and safety PT KTS. This can be proven from company data, namely the number of work accident rates in the company's production process is very small. In addition, the level of compliance of employees of PT. KTS towards implementing occupational health and safety programs can be implemented properly.